(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
This is a pure and Scandium (Sc+3), Manganese (Mn+3) were added to ZnO in different ‎controlled percentages Zn‏)‏‎1-x‏(‏‎ ScxO, Zn‏)‏‎1-x‏(‏‎ MnxO. Synthesized using a co-precipitation ‎technique. Particularly, it was demonstrated that several novel and intriguing physical ‎properties. These were created by means of a combination of morphological-structural and ‎optical research. X-ray diffraction research explained that the ZnO hexagonal wurtzite ‎structure was preserved alongside the (002) preferred crystallized plane for ZnO with (Sc,‎Mn)ions added .The particles were examined using field emission scanning electron ‎microscopy shows the hemispherical shape and shows the increase in amount of manganese, ‎as well the higher agglomeration. A distinct magnetization was indicated by the vibrating ‎sample magnetometer test, which was utilized to obtain the hysteresis loops. ZnO-NPs ‎showing at room temperature ferromagnetic (RTFM) characteristic.‎